Our existential dilemma: Bor orBe'er - Goodnick, Benjamin (Journal of religion and health, 1989)
An evaluation is made of the choices available to individuals in dealing with their essential alone-ness, the existential dilemma; and a parallel is drawn between these choices and flowing and stagnant waters, as interpreted by traditional sources.